Exploration of rapid start-up of the CANON process from activated sludge inoculum in a sequencing biofilm batch reactor (SBBR) - Deng, Yangfan (Water science and technology : a journal of the International Association on Water Pollution Research, 2016)
In this study, a laboratory-scale sequencing biofilm batch reactor (SBBR) was employed to explore a fast start-up of completely autotrophic nitrogen removal over nitrite (CANON) process. Partial nitrification was achieved by controlling free ammonia concentration and operating at above 30 °C; then the reactor was immediately operated with alternating periods of aerobiosis and anaerobiosis to start the anammox process. The CANON process was successfully achieved in less than 50 d, and the total-nitrogen removal efficiency and the nitrogen removal rate were 81% and 0.14 kg-N m(-3) d(-1) respectively. Afterwards, with the increasing of ammonium loading rate a maximum nitrogen removal rate of 0.39 kg-N m(-3) d(-1) was achieved on day 94. DNA analysis showed that 'Candidatus Brocadia' was the dominant anammox species and Nitrosomonas was the dominant aerobic ammonium-oxidizing bacteria in the CANON reactor. This study revealed that due to shortening the persistent and stable nitrite accumulation period the long start-up time of the CANON process can be significantly reduced